2006
DOI: 10.1039/b517538k
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and structural studies on C-ethynyl- and C-bromo-carboranes

Abstract: A high-yield preparation of the C-monoethynyl para-carborane, 1-Me(3)SiC[triple bond]C-1,12-C2B10H11, from C-monocopper para-carborane and 1-bromo-2-(trimethylsilyl)ethyne, BrC[triple bond]CSiMe(3) is reported. The low-yield preparation of 1,12-(Me3SiC[triple bond]C)2-1,12-C2B10H10 from the C,C'-dicopper para-carborane derivative with 1-bromo-2-(trimethylsilyl)ethyne, BrC[triple bond]CSiMe3, has been re-investigated and other products were identified including the C-monoethynyl-carborane 1-Me3SiC[triple bond]C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…The protected acetylenes 2 and 6 were likewise obtained from sequential reaction of 8 and 10 with methyllithium and chlorotrimethylsilane. The overall yields of 1, 2, 6 and 7 from para-carboranes 3 and 5 are 69%, 67%, 63% and 48%, respectively, which are superior to reported yields of up to 26% from previous single/two-step syntheses [6][7][8]10]. The convenience of a two-step route is also an obvious advantage in effort and cost over the more elaborate multi-step syntheses, which afford the ethynyl carboranes in comparable yield to those described here [9].…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…The protected acetylenes 2 and 6 were likewise obtained from sequential reaction of 8 and 10 with methyllithium and chlorotrimethylsilane. The overall yields of 1, 2, 6 and 7 from para-carboranes 3 and 5 are 69%, 67%, 63% and 48%, respectively, which are superior to reported yields of up to 26% from previous single/two-step syntheses [6][7][8]10]. The convenience of a two-step route is also an obvious advantage in effort and cost over the more elaborate multi-step syntheses, which afford the ethynyl carboranes in comparable yield to those described here [9].…”
Section: Resultsmentioning
confidence: 56%
“…A low-yielding synthesis of 2 has been reported by Kaszynski et al [8] while we have also used 1-bromo-3-methyl-1-butyn-3-ol instead of 4 in a two-step synthesis of 1 in low yields [7]. Herzog et al reported multi-step syntheses of 1 and 2 from 3 in overall yields of 64% [9].…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…[19] In contrast, a number of dicarba-closo-dodecaboranes with ethynyl groups or other alkynyl substituents bonded to carbon were structurally characterized. [2,[27][28][29][30][31][32] In Figure 1 the diethynyl-substituted clusters 1a and 3a are depicted. The CϵC and B-C bond lengths of 1a and 3a are similar (Table 1) and they are also similar to bond lengths determined for ethynyl groups bonded to boron of different clusters, for example, in the anion [12-HCC-closo-1- [33] ( [34] The differences of the experimentally determined d(CϵC) of the ethynyl-functionalized boron clusters listed in Table 1 are small and not significant (Ͻ3σ).…”
Section: Single-crystal Structures Of 1a 3a and 2bmentioning
confidence: 99%